DAMPAK TERHADAP KONSUMEN DARI PERSAINGAN BISNIS TIDAK SEHAT PARA PELAKU USAHA SEPEDA MOTOR - TUTIEK RETNOWATI; DENALDI FERNANDO (Jurnal HUKUM BISNIS, 2020)
Every business actor in Indonesia must be in a situation of fair and fair business competition, so as not to cause a concentration of economic power on certain business actors, by still obeying various existing laws and regulations in force in the State of Indonesia. In addition, in principle in the business world, efforts to obtain the maximum profit is a reasonable behavior, as long as it does not cause monopolistic practices and unfair business competition. If that happens in Indonesia, of course it will also be detrimental to the Indonesian people in general as consumers Keywords: business competition, business actors, motorbikes